Dr. Seuss' The Cat in the Hat [videorecording (DVD)] - Welch, Bo; Myers, Mike, 1963-; Baldwin, Alec, 1958-; Preston, Kelly; Fanning, Dakota, 1994-; Hayes, Sean, 1970-; Geisel, Theodor Seuss, 1904-1991 (Universal, 2004)
Conrad and Sally Walden are home alone with their pet fish. It is raining outside, and there is nothing to do. Until The Cat in the Hat walks in the front door. He introduces them to their imagination, and at first it's all fun and games, until things get out of hand and the kids wreak havoc in the home their mother has neatly prepared for an upcoming party. So The Cat must go, go, go, before their parents get back.